Sexualidade e educação sexual: prática docente em uma escola pública de Juazeiro do Norte - CE - Quirino, Glauberto da Silva (2012)
Ethnographic study adapted to education that aimed to investigate the actions and relation of teachers and their daily work in sex education of adolescents in primary and secondary schools that configure the educational praxis of school experience and the specific objectives were: identify the teachers approach on sex education at school in the perception of adolescents; characterize the adolescents from the social and sex point of view; know the teachers' perception on sexuality and sex education; describe the teachers' work on sex education in a public school of Juazeiro do Norte- CE, Brazil; and, learn their values and attitudes toward adolescents' sexuality in school environment. The fieldwork was carried out from September 2009 to February 2010 through a questionnaire answered by 67 students, followed by observation and semi-structured interviews with seven teachers that had their classes observed. Questionnaire data was organized through the Collective Subject Discourse Method, teachers' perception of sexuality and sex education through thematic categorization. The analysis happened in a reflective and interpretive way. The students reported that the teachers usually did not approach the issues in classroom and when it was present it was predominantly in biological sciences, guided by the prerogative of preventing sexually transmitted infections. The concept of sexuality was divided in two categories: gender and sexual orientation. Besides physical aspects, there was spiritual elements and expression of love between humans, although these were secondary to the attributes of genitals and sexual intercourse, surrounded by the natural character. Sex education was based on three themes: sexual intercourse, body physiology and social behavior. Science classes figured as the most appropriate place to discuss the matter. It was found that even though the issues were raised by the students, the teachers were always omitted in any intervention. We verified the presence of moral and personal values in the conduction of educational practices, silence concerning the prejudice against homosexuals and the loss of virginity, as well as maintenance of gender inequalities. The approach on sexuality in the school environment does not happen in a cross-sectional way. The pedagogical practice was configured as sexist in a gender environment that uses silencing as a way of disciplining and controlling sexuality, as well as for the maintenance of hegemonic order, producing and reproducing the values and attitudes of the patriarchal and sexist society model. Thus, the teaching work needs constant renewal, being necessary to overcome the biomedical/scientific model on sexuality, considering its historical, social and cultural dimensions, whose crosssectional actions should be seek in various fields of knowledge.